Chronic corticosterone exposure disrupts hepatic and intestinal bile acid metabolism in chicken - Wu, Lei; Liu, Xinyi; Zhang, Aijia; Chen, Huimin; Zhao, Ruqian; Jia, Yimin (Frontiers in Veterinary Science, 2023)
Objective Chronic stress leads to a high circulating level of glucocorticoids, which disrupts lipid metabolism and causes non-alcoholic fatty liver disease in mice and humans. Meanwhile, bile acid (BA), a class of metabolites initially synthesized in the liver and further metabolized by gut microbiota, plays a vital role in lipid metabolism. This study aimed to investigate the effects of glucocorticoids on BA metabolism and gut microbiota in chickens. Methods In this study, 35-day-old chickens were injected with 4 mg/kg/day corticosterone (Cort) for 14 days to simulate chronic stress. Results Cort treatment significantly increased the triglyceride contents in the plasma and the liver. HE and oil-red staining showed that Cort treatment induced fatty liver in chickens. Meanwhile, Cort exposure downregulated total bile acid (TBA) content in the liver while increasing the TBA in feces. UPLC-HRMS results showed that Cort exposure significantly decreased the hepatic levels of CDCA, T-alpha-MCA, and T-beta-MCA. Moreover, Cort exposure significantly reduced the expression of genes related to BA synthesis (CYP8B1 and CYP27A1), conjugation (BACS), and regulation (KLβ and FGFR4). 16s sequencing results showed that Cort treatment significantly decreased the amount of Lachnospiraceae, Eisenbergiella, Blautia, and Eubacterium and increased the abundance of Barnesiella, Lactobacillus, and Helicobacter. Spearman correlation analysis showed a significant positive correlation between fecal TBA and the abundance of Lactobacillales, Lactobacillus, and Barnesiella. In comparison, TBA in the liver was positively correlated with Eubacterium, and negatively correlated with Helicobacter. Conclusion In summary, chronic Cort exposure disrupts hepatic and intestinal bile acid metabolism inducing gut microbiome dysbiosis, which might associate with the development of fatty liver in chickens.